Sociotechnical imaginaries of energy transition: The case of the Portuguese Roadmap for Carbon Neutrality 2050 - Carvalho, António (2022)
This article analyses sociotechnical imaginaries of energy transition emerging from the Portuguese Roadmap for Carbon Neutrality 2050 (RNC2050). It expands literature on the articulations between sociotechnical imaginaries and energy transitions by introducing the Portuguese context and delving into an original and understudied case study – the RNC2050. We contend that the RNC2050 illustrates how energy transitions enable multiple – and, often times, conflicting – sociotechnical imaginaries, which, in turn, outline diverse associations between science, society and politics to address the climate crisis. By exploring how distinct actors and social groups resort to the RNC250 to support their own understandings and pathways to carbon neutrality, we argue that this document can be interpreted as a boundary object. We conducted nineteen semi-structured interviews and one informal conversation with members from three different stakeholder groups (the RNC2050 execution team; political entities; civil society). Drawing on our empirical data, four sociotechnical imaginaries were identified – Modernization and Techno-Economic Development; Green Economy; Energy Citizenship; Just Transition – and characterized, detailing their key features and associated stakeholders. We discuss our results highlighting six relevant aspects: the situatedness of stakeholders; the RNC2050 as a boundary object; dynamics of inclusion/exclusion, counter-hegemonic imaginaries, and power issues; the co-option of subaltern imaginaries; and the evolution of imaginaries across time. Although arising from the Portuguese context, we contend that these results are relevant for energy transitions research more broadly, as well as for energy transition policymakers. We conclude by presenting some of the policy implications of our study.